2002
DOI: 10.1021/np0101651
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cytotoxic Lignans from Justicia procumbens and Their Effects on Nitric Oxide and Tumor Necrosis Factor-α Production in Mouse Macrophages

Abstract: A new lignan glycoside, 4-O-alpha-L-arabinopyranosyl-(1' "-->2' ')-beta-D-apiofuranosyldiphyllin (2), named procumbenoside A, and 11 known compounds were isolated from the whole plant of Justicia procumbens. The structure of 2 was established by spectral analysis and chemical methods. The known compounds justicidin A (1), diphyllin (3), and tuberculatin (4) showed potent cytotoxic effects against a number of cancer cells in vitro. Compounds 1 and 4 also strongly enhanced tumor-necrosis factor-alpha (TNF-alpha)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 16 publications
3
68
1
Order By: Relevance
“…Justicidin A, an arylnaphthalide lignan isolated from the acanthaceous plant Justicia procumbens (Fukamiya and Lee, 1986), has been shown to have strong antiviral activity (Asano et al, 1996), potent cytotoxic effects (Day et al, 1999(Day et al, , 2002, and enhanced TNF-␣ generation in LPS-stimulated RAW 264.7 cells at lower concentrations (Յ1 M justicidin A) (Day et al, 2002). Surprisingly, we found that at concentrations greater than 5 M, justicidin A significantly inhibited LPS-stimulated TNF-␣ secretion in the present study.…”
contrasting
confidence: 80%
“…Justicidin A, an arylnaphthalide lignan isolated from the acanthaceous plant Justicia procumbens (Fukamiya and Lee, 1986), has been shown to have strong antiviral activity (Asano et al, 1996), potent cytotoxic effects (Day et al, 1999(Day et al, , 2002, and enhanced TNF-␣ generation in LPS-stimulated RAW 264.7 cells at lower concentrations (Յ1 M justicidin A) (Day et al, 2002). Surprisingly, we found that at concentrations greater than 5 M, justicidin A significantly inhibited LPS-stimulated TNF-␣ secretion in the present study.…”
contrasting
confidence: 80%
“…Justicidin A was isolated from J. procumbens plants [9]. DiOC 6 (3) was obtained from Molecular Probes (Eugene, OR).…”
Section: Methodsmentioning
confidence: 99%
“…Justicia procumbens (J. procumbens) is a traditional herbal remedy in Taiwan for fever, pain, and cancer [6,7]. Justicidin A, purified from a methanolic extract of J. procumbens, has various biological activities including suppression of tumor cell growth [8,9] and release of TNF-a [10]. The purpose of present study was to determine whether apoptosis is stimulated by justicidin A-treatment of human HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Lignans 30, 31, and 37, isolated from J. ciliata, showed significant citotoxic effects toward a number of cancer cell types (human hepatomacellular carcinoma, human cervical carcinoma, human colorectal adenocarcinoma, human colorectal carcinoma, and human breast cancer) (Day et al, 2002). Lignan 31 also displayed potent cytotoxic effects against T-24, CaSki, SiHa, HT-3, PLC/PRF/5, and 212 cells in vitro (Day et al, 1999).…”
Section: Biological Activity Of Compounds Isolated From Species Of Jumentioning
confidence: 98%